Market segment-driven housing affordability criteria for housing programs in Nigeria: An arrow in the quiver? - Chuka Uzoma Ifediora; Geraldine Ugwuonah (International Journal of Technology for Business (IJTB), 2019)
This paper sought to conceptualize the adoption of market segmentation strategy in the design of efficient housing program affordability criteria in Nigeria. Affordability of housing is a critical issue facing the actualization of the basic human need for shelter in a developing nation, such as Nigeria. This article drew from some previous market segmentation studies to develop a conceptual model of housing program affordability criteria that incorporates the process of market segmentation in the design and implementation of housing program affordability criteria. The conceptual model presented in this paper, provides a unique, pragmatic and helpful structure, for understanding how multiple affordability criteria that reflect the needs of target segments of a housing program could be developed and implemented using market segmentation strategy.
Keywords: 650; Market Segmentation; Housing Affordability; Housing Needs; Housing Program; Market Segment-Driven